A comparison of the efficiency of riverbank filtration treatments in different types of wells - Górski, Józef; Dragon, Krzysztof; Kruć, Roksana (Geologos, 2018)
In the paper, a comparison of the efficiency of riverbank treatments is outlined for the Krajkowo well field, where different methods of water abstraction are used. The water is extracted from 29 vertical wells that are located at a distance of 60–80 m from the channel of the River Warta and from a horizontal well with radial drains located 5 m below the bottom of the river. The results of a two-year water-quality investigation indicate that the water quality in both types of abstraction system is influenced by the quality of river water. The water quality observed in the horizontal well is closely similar to that of the river water, with similar concentrations of sulphates, nitrates and micropollutants, but a reduction in bacteriological contamination and plankton is clearly seen. The reduction in contaminants is mainly the result of physical processes, such as mechanical entrapment of suspended material and colloids as well as bacteria and plankton. In the vertical wells, the influence of contamination from river water is also visible, but the reduction in contamination is more significant, especially in cases of bacteria, plankton, micropollutants and nitrates, and is determined by both physical and chemical processes, such as sorption, dissolution, red-ox processes and denitrification. The present research shows that river water treatment is more effective in the case of vertical wells. The most favourable distance of a well from the channel of the river, from the perspective of water quality, is 150–200 m, which corresponds to a residence time of about six months.